The Point of the Message is Something different: Comments on the article of András Simonovits entitled: Family allowance and pension dependent on the number of children: optimality and neutrality - Banyár, József (Public Finance Quarterly, 2020)
The polemic article of András Simonovits , published in the current issue (Simonovits, 2020), was particularly fast: he reacted to my paper published in the previous issue – even before its publication – by always showing me the current stage of his article while he was continuously elaborating it, and sometimes (but generally not) taking my comments and recommendations. The reason why I can respond so fast to his article published herein is that he immediately shared with me the final version accepted by the quarterly, for which I am thankful to him. The article does not contain any particular criticism. Actually, it illustrates the extreme cases of my theory and adds some subtlety, which is achieved by the introduction of child specific consumption φ. His main problem is that I do not substantiate my message with a mathematical model, and that with my article I distract the attention from other more important topics. We can argue about the usefulness of mathematical models; I think I will need them at a later stage of the detailed explanation of my theory, but at this stage they would only be impediments. As far as the diversion of attention is concerned, that is clearly a misconception. In my response article, I will demonstrate that the point of my message is something totally different from what Simonovits thinks it is, and also that my point is difficult to grasp with his model. The essential difference is that I do not primarily address the lifetime optimisation of individual consumption (including the pension system), but the contradictions of the pension system. Nonetheless, I will try to present my actual statements.